Pengaturan Pemberhentian Presiden dalam Masa Jabatan Menurut UUD 1945 (Studi Komparatif Sebelum dan Sesudah Perubahan) - Syawawi, Reza (Jurnal Konstitusi, 2010)
In terms of the constitutional basis, the impeachment of the President in his tenure has been set substantially on the third amandement 1945 (2001) which was ratified on November 9, 2001. The process of the president impeachment is no longer entirely left to the political mechanism, but based on legal mechanisms as provided in Article 7a and 7b the 1945 constitution. Besides relating to the violated of law, the impeachment of  the President in his tenure is also possible if the president is no longer qualify as a president as stated in Article 6 of the 1945 constitution.